Pneumonia - Simone Dini; Federica Sganga; Mattia Brunori; Aurora Vitali; Annalisa Paglia; Giulia Mussatti (Geriatric Care)
Pneumonia is a very frequent problem for old frail patients due to diffusion, mortality, and other negative outcomes. The most complex aspects consist of the formulation of a diagnosis and the choice of an adequate treatment. In this context, optimal management requires the correct definition of the category and the most probable etiology involved in choosing the empiric treatment. Following this, it is crucial to conduct accurate examinations and, whenever feasible, switch to targeted treatments, ensuring timely adoption of oral administration.